Analysis of Ds⁎D⁎K⁎ and Ds1D1K⁎ Vertices in Three-Point Sum Rules - M. Janbazi; R. Khosravi; E. Noori (Advances in High Energy Physics)
In this study, the coupling constants of Ds⁎D⁎K⁎ and Ds1D1K⁎ vertices were determined within the three-point Quantum chromodynamics sum rules method with and without consideration of the SUf(3) symmetry. The coupling constants were calculated for off-shell charm and K⁎ cases. Considering the nonperturbative effect of the correlation function, as the most important contribution, the quark-quark, quark-gluon, and gluon-gluon condensate corrections were estimated and were compared with other predictive methods.